Epigenetic Modifications Associated with Abiotic and Biotic Stresses in Plants: An Implication for Understanding Plant Evolution - Barbara Hohn (Frontiers Research Topics, 2018)
Alterations in gene expression are essential during growth and development phases and when plants are exposed to environmental challenges. Stress conditions induce gene expression modifications, which are associated with changes in the biochemical and physiological processes that help plants to avoid or reduce potential damage resulting from these stresses.After exposure to stress, surviving plants tend to flower earlier than normal and therefore transfer the accumulated epigenetic information to their progenies, given that seeds, where this information is stored, are formed at a later stage of plant development.DNA methylation is correlated with expression repression. Likewise, miRNA produced in the cell can reduce the transcript abundance or even prevent translation of mRNA. However, histone modulation, such as histone acetylation, methylation, and ubiquitination, can show distinct effects on gene expression. These alterations can be inherited, especially if the plants are consistently exposed to a particular environmental stress. Retrotransposons and retroviruses are foreign movable DNA elements that play an important role in plant evolution. Recent studies have shown that epigenetic alterations control the movement and the expression of genes harbored within these elements. These epigenetic modifications have an impact on the morphology, and biotic and abiotic tolerance in the subsequent generations because they can be inherited through the transgenerational memory in plants. Therefore, epigenetic modifications, including DNA methylation, histone modifications, and small RNA interference, serve not only to alter gene expression but also may enhance the evolutionary process in eukaryotes.In this E-book, original research and review articles that cover issues related to the role of DNA methylation, histone modifications, and small RNA in plant transgenerational epigenetic memory were published.The knowledge published on this topic may add new insight on the involvement of epigenetic factors in natural selection and environmental adaptation. This information may also help to generate a modeling system to study the epigenetic role in evolution.